2023
DOI: 10.3390/molecules28124643
|View full text |Cite
|
Sign up to set email alerts
|

Terpinen-4-ol Induces Ferroptosis of Glioma Cells via Downregulating JUN Proto-Oncogene

Abstract: According to previous research, turmeric seeds exhibit anti-inflammatory, anti-malignancy, and anti-aging properties due to an abundance of terpinen-4-ol (T4O). Although it is still unclear how T4O works on glioma cells, limited data exist regarding its specific effects. In order to determine whether or not glioma cell lines U251, U87, and LN229 are viable, CCK8 was used as an assay and a colony formation assay was performed using different concentrations of T4O (0, 1, 2, and 4 μM). The effect of T4O on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Among the various mechanisms investigated in ferroptosis research, lipid peroxidation, which leads to the generation of lipid oxidation products, has garnered substantial attention. Cao et al ( 51 ) discovered that the overexpression of JUN significantly suppressed the impact of T4O on both glioma cell proliferation and ferroptosis. Luo et al ( 52 ) demonstrated that MAPK8 could reverse the impact of LINC01564 ablation on both cell apoptosis and ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various mechanisms investigated in ferroptosis research, lipid peroxidation, which leads to the generation of lipid oxidation products, has garnered substantial attention. Cao et al ( 51 ) discovered that the overexpression of JUN significantly suppressed the impact of T4O on both glioma cell proliferation and ferroptosis. Luo et al ( 52 ) demonstrated that MAPK8 could reverse the impact of LINC01564 ablation on both cell apoptosis and ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of colony growth, Cao et al (2022) showed that terpinen-4-ol decreased the colony formation ability of pancreatic cells AsPC-1 and PANC-1 [17]. Furthermore, Cao et al ( 2023) corroborated the inhibitory effect of terpinen-4-ol on colony formation in glioma cancer cells U251, T98, and LN229 [22].…”
Section: The Four Monoterpenes Inhibited Nsclc Cellular Viability And...mentioning
confidence: 95%
“…With the rising interest in alternative and complementary approaches to conventional cancer therapies, exploring the therapeutic potential of natural compounds is crucial. Natural compounds such as curcumin, fucoxanthin, terpinen-4-ol, Boric acid and dihydroartemisinin, have been found to possess remarkable anti-cancer properties, including the ability to induce ferroptosis (44)(45)(46)(47)(48). These compounds target ferroptosis through various mechanisms, including iron metabolism, glutathione peroxidase 4, and the cystine/glutamate antiporter system.…”
Section: Natural Chemicals Targeting Ferroptosismentioning
confidence: 99%